The ethical implications of 4IR. Issue 1 (14th August 2021) - Peckham, Jeremy Burford
Abstract : Purpose: This paper aims to highlight the ethical implications of the adoption of Fourth Industrial Revolution (4IR) technologies, particularly artificial intelligence (AI), for humanity. It proposes a virtues approach to resolving ethical dilemmas. Design/methodology/approach: The research is based on a review of the relevant literature and empirical evidence for how AI is impacting individuals and society. It uses a taxonomy of human attributes against which potential harms are evaluated. Findings: The technologies of the 4IR are being adopted at a fast pace, posing numerous ethical dilemmas. This study finds that the adoption of these technologies, driven by an Enlightenment view of progress, is diminishing key aspects of humanity – moral agency, human relationships, cognitive acuity, freedom and privacy and the dignity of work. The impact of AI algorithms is also shown, in particular, is shown to be distorting the view of reality and threatening democracy, in part due to the asymmetry of power between Big Tech and users. To enable humanity to be masters of technology, rather than controlled by it, a virtues-based approach should be used to resolve ethical dilemmas, rather than utilitarian ethics. Research limitations/implications: Further investigation is required to provide more empirical evidence of the harms to humanity of some 4IR technologies cited, such as virtual and augmented reality, manipulative algorithms and toy robots on children and adults and the reality of re-skilling where jobs are lost through automation. Practical implications: This paper provides a framework for evaluating the impact of some 4IR technologies of humanity and an approach to resolving ethical dilemmas. Social implications: Most of the concerns surrounding 4IR technologies, and in particular AI, tend to focus on human rights issues. This paper shows that there are other significant harms to what it means to be a human being from 4IR technologies that will have a profound impact on society if not adequately addressed. Originality/value: The author is not aware of any other work that uses taxonomy of AI applications and their different impacts on humanity. The proposal to use virtues as a means to resolve ethical dilemmas is also novel in regard to AI.